Ceria-Based Materials in Hydrogenation and Reforming Reactions for CO2 Valorization - Boaro, Marta; Colussi, Sara; Trovarelli, Alessandro (Frontiers in Chemistry, 2019)
Reducing greenhouse emissions is of vital importance to tackle the climate changes and to decrease the carbon footprint of modern societies. Today there are several technologies that can be applied for this goal and especially there is a growing interest in all the processes dedicated to manage CO2 emissions. CO2 can be captured, stored or reused as carbon source to produce chemicals and fuels through catalytic technologies. This study reviews the use of ceria based catalysts in some important CO2 valorization processes such as the methanation reaction and methane dry-reforming. We analyzed the state of the art with the aim of highlighting the distinctive role of ceria in these reactions. The presence of cerium based oxides generally allows to obtain a strong metal-support interaction with beneficial effects on the dispersion of active metal phases, on the selectivity and durability of the catalysts. Moreover, it introduces different functionalities such as redox and acid-base centers offering versatility of approaches in designing and engineering more powerful formulations for the catalytic valorization of CO2 to fuels.